2021
DOI: 10.3390/jcm10102132
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Effectiveness of Empirical Anti-TNF Dose Intensification in Inflammatory Bowel Disease: Systematic Review with Meta-Analysis

Abstract: Loss of response to antitumor necrosis factor (anti-TNF) therapies in inflammatory bowel disease occurs in a high proportion of patients. Our aim was to evaluate the loss of response to anti-TNF therapy, considered as the need for dose intensification (DI), DI effectiveness and the possible variables influencing its requirements. Bibliographical searches were performed. Selection: prospective and retrospective studies assessing DI in Crohn’s disease and ulcerative colitis patients treated for at least 12 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 187 publications
0
11
0
Order By: Relevance
“…Finally, a significant proportion of patients lost the response to the second anti-TNF in the long term, although increasing the dose was an effective strategy for regaining response in some cases. Dose escalation in patients who lose the response to anti-TNF drugs is effective and common in clinical practice [40,41]. However, there are insufficient data to recommend dose optimisation strategies in patients who do not respond to the second anti-TNF drug and experienced primary failure with the first one.…”
Section: Studies Evaluating the Efficacy Of Switching To A Second Anti-tnf Agent In Primary Failures To A First Onementioning
confidence: 99%
“…Finally, a significant proportion of patients lost the response to the second anti-TNF in the long term, although increasing the dose was an effective strategy for regaining response in some cases. Dose escalation in patients who lose the response to anti-TNF drugs is effective and common in clinical practice [40,41]. However, there are insufficient data to recommend dose optimisation strategies in patients who do not respond to the second anti-TNF drug and experienced primary failure with the first one.…”
Section: Studies Evaluating the Efficacy Of Switching To A Second Anti-tnf Agent In Primary Failures To A First Onementioning
confidence: 99%
“…14 A recent analysis of numerous studies examining the need for IFX dose escalation in IBD showed that patients with UC more often required dose escalation than patients with Crohn's diseas. 15 However, attempts to alter the dosing regimen and accelerate the induction strategy in severe UC have produced inconclusive results. A small retrospective analysis of 50 patients with severe UC showed that the accelerated induction strategy of IFX reduces the need for an early colectomy.…”
Section: Dosage Of Infliximab and Drug Therapeutic Windowmentioning
confidence: 99%
“…49 An alternative to reactive monitoring is empirical dose escalation based on clinical symptoms alone and this has also been shown to be relatively beneficial. 50 However, reactive TDM of biologics is ultimately recommended as the new standard of care as it enables the most rational therapeutic decisions to be undertaken. 37 An important advantage of TDM is not only the possibility to determine the extent to which treatment should be escalated but also to identify patients who will not benefit from dosage increase due to normal drug levels or the presence of high antibody titers.…”
Section: Reactive Monitoring Of Infliximab Treatmentmentioning
confidence: 99%
“…Two recent systematic reviews, one of which also undertook a meta-analysis, evaluated the clinical effectiveness of anti-TNF dose intensification to address LOR across Crohn’s disease and ulcerative colitis. 8,9 While comprehensive in their approach, neither review distinguished between anti-TNF dose intensification undertaken to address secondary LOR and anti-TNF dose intensification undertaken to address pooled primary non-response and secondary LOR. It is, however, important to differentiate between both of these entities, given the disparate clinical effectiveness of anti-TNF dose intensification between primary responders and primary non-responders.…”
Section: Introductionmentioning
confidence: 99%